Governing higher education institutions in Singapore: an agency framework - Sam, Choon-Yin (Serbian Journal of Management, 2016)
It is widely known that governments are changing their relationships with public sector organizations with the aim of improving public sector efficiency and effectiveness. The conceptual understanding of government control and governance approaches in state-owned higher education institutions (HEIs) is, however, less well understood. Undoubtedly, question of the extent of autonomy and control of higher education institutions is of significant interest to administrators and policy-makers. This paper reviews the reforms undertaken by the Singapore government in HEIs especially the university sector. The agency framework is applied to assess the internal and external monitoring mechanisms aimed to protect the interest of the public. The paper finds that there is still much state presence and intervention in HEIs’ activities despite the government’s attempt to develop autonomous universities. Strengthening the corporate governance standard of the HEIs will offer a useful means to increase the willingness of the government to give more control to the HEI administrators.